Pre-Service English Teachers’ Perception towards Online Assessment Method - Marisa Yoestara; Zaiyana Putri; Meta Keumala; Zahratul Idami (IJELR: International Journal of Education, Language, and Religion, 2020)
This study aims to figure out pre-service English teachers’ perception towards online testing system. In this study, the writers employed questionnaire to collect the data, and it was distributed to a total of 82 English Department students in Banda Aceh and Langsa City, Aceh. The questionnaire was developed based on a relevant previous study’s questionnaire, and in this study, the questionnaire itself was conducted in Google form consisted of 13 questions that asked about the university students’ perception about online test. Then all obtained data were analyzed by using percentage formula. The findings indicate that63% or 55 respondents have positive perception toward online assessment. On the other hand, the negative perception goes to the other 37% or 27 respondents.